Habituasi Karakter Siswa: Konstruksi Budaya Sekolah dalam Membentuk Sikap Disiplin dan Tanggung Jawab - Rosita Rosita; Riri Putri Apriliani; Dini Amallya; Jepri Utomo; Mila Noviana (Kampus Akademik Publiser, 2026)
School culture is a set of values, norms, habits, and interaction patterns that develop within the educational environment and play a significant role in shaping students’ character. A positive school culture can foster students’ internalization of social values such as discipline, responsibility, cooperation, tolerance, honesty, and respect in their daily lives. This study aims to analyze how school culture plays a role in shaping students’ attitudes of discipline and responsibility through various activities implemented within the school environment. The method used is a literature review, examining various journals, scientific articles, and relevant sources that discuss school culture in shaping students’ attitudes of discipline and responsibility. School culture plays a role in shaping students’ character of discipline and responsibility through teacher role models, the implementation of school rules, routine activities, positive habits, and the creation of harmonious social interactions among school members. A conducive school environment can encourage students to understand, apply, and maintain social values in various social situations, both at school and in the community. Conversely, a less supportive school culture can hinder students’ social development and character. Thus, school culture is a crucial factor in developing a generation that not only excels academically but also possesses strong character traits of discipline and responsibility. Strengthening a positive school culture needs to be continuously developed as part of efforts to improve the quality of character education in schools.